Effectiveness of manual therapy in COPD: A systematic review of randomised controlled trials - C. Simonelli; M. Vitacca; M. Vignoni; N. Ambrosino; M. Paneroni (Pulmonology, 2019)
Purpose: Manual therapy (MT) has been proposed in pulmonary rehabilitation programmes for patients with chronic obstructive pulmonary disease (COPD), but an updated systematic review of the evidence is lacking. We aimed to systematically review the effectiveness of MT interventions, alone or added to exercise, on lung function, exercise capacity and quality of life in COPD patients, compared to other therapies (e.g. exercise alone) or no treatment. Materials and methods: We searched MEDLINE, EMBASE, Physiotherapy Evidence Database, and Cochrane Central Register of Controlled Trials databases, using the terms: COPD, manual therapy, manipulation, joint mobilisation, osteopathic manipulation. Only randomised controlled trials (RCT) were considered. Results: Out of 555 articles screened, 6 fulfilled the inclusion criteria. The study designs were heterogeneous (with different intervention schedules) and there was a high risk of bias. No effect on lung function was found, while results on exercise capacity were contrasting. MT had no effect on quality of life, although valid measures were available only in one study. Only mild adverse events were reported. Conclusions: Few RCTs of poor methodological quality are available on the effects of MT in COPD. More and better quality RCTs are needed before this technique can be included in rehabilitation programmes for these patients. Keywords: Chronic obstructive pulmonary disease, Manual therapy, Manipulation, Pulmonary rehabilitation, Physiotherapy